Preliminary approach to detect amylolytic and pectinolytic activities from maca (Lepidium meyenii Walp.) (Revista Brasileira de Ciências Farmacêuticas, 2006)
Amylase (AM), pectinesterase (PE) and polygalacturonase (PG) were extracted from maca roots (Lepidium meyenii Walp). The response surface model was used to determine the optimum conditions of pH and temperature activity of each enzyme on the crude extract. The highest values of AM activity occurred at pH 6.1 and 33.6 °C, very close to the experimental central point. The PE activity had a maximum activity at pH 6.6 and 49.4 and PG activity showed optimum activity at pH 5.4 and 46 °C.